DAMPAK PENERAPAN PSAK 50, PSAK 55 DAN PSAK 60 (REVISI) PADA PENYISIHAN KERUGIAN KREDIT PERBANKAN - Rahmadhani, Sari (STIE Totalwin Semarang, 2014)
Bank Indonesia, together with the financial accounting standards board issued financial standards governing the allowance for credit losses due to the enactment of the international financial standards IFRS. Provision for credit losses is very important for banks to be able to cope with the risk of losses incurred due to the failure of the bank disbursed loan repayments. Banking indirectly still have a dilemma with the application of IAS 50 on financial instruments presentation of IAS 55 and IAS 60 regarding measurement of the disclosure. These applications have benefits in addition to the problems in the implementation.